Constructing Ebola martyrs, warriors, and saviours: online heroisation in a context of risk and unease. (17th February 2021) - Roy, Melissa; Moreau, Nicolas; Rousseau, Cécile; Mercier, Arnaud; Wilson, Andrew; Dozon, Jean-Pierre; Atlani-Duault, Laëtitia
Abstract : The perception of epidemic risk has been associated with the production of narratives in which figures such as villains and heroes emerge. This article critically analyzes social media users' construction of heroic figures during the 2013–2016 Ebola epidemic. We used international Twitter and Facebook comments as our raw material, collected by key word extraction. A thematic analysis resulted in a descriptive typology of three heroic figures: the martyr, the warrior, and the saviour. Our analysis showed that heroic status (highly associated with willingness to take high risks on behalf of others) was mostly conferred on common individuals and 'insiders' living in the Ebola-afflicted communities – often deemed 'unsung' – rather than the foreigners frequently heroised in previous crises. We deconstruct this heroisation dynamic, showing that it is a socially strategic move because it is embedded in a potential instrumentalization of heroes. First, this production of 'everyday heroes' may encourage the involvement of lay people in the epidemic response, by conveying that anyone can become a health hero. Second, we show that this heroisation process maintains the status quo by encouraging adherence to biomedical discourses, and by individualising the narrative and neglecting the structural changes needed to address the epidemic. Finally, we caution against discourses that seem socially 'progressive' but may be used as a smokescreen to hide discriminatory dynamics, and we recommend changes in communication strategies.